(untitled) - Vietnam Development Forum (Hà Nội, 2007)
This book contains selected papers from the National Project, namely "Assessment of TechnologicalImpacts on Economic Growth and Productivities in Vietnam" conducted during 2004-2006. The book is related the field of research and provided crucial information about Vietnamese economy and the current development of economic sector, the technological development.